2013
DOI: 10.1186/1745-6215-14-93
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone text message intervention to reduce binge drinking among young adults: study protocol for a randomized controlled trial

Abstract: BackgroundHeavy episodic (binge) drinking is common among young adults and can lead to injury and illness. Young adults who seek care in the Emergency Department (ED) may be disproportionately affected with binge drinking behavior, therefore provide an opportunity to reduce future risk through screening, brief intervention and referral to treatment (SBIRT). Mobile phone text messaging (SMS) is a common form of communication among young adults and has been shown to be effective at providing behavioral support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Further, it extends previous research in this area [12,38], which has applied limited tailoring of message content for SMS-based brief interventions. Participants in this trial have been screened multiple times for risky drinking behavior, and as such, are an ideal cohort to target with an intervention.…”
Section: Discussionsupporting
confidence: 68%
“…Further, it extends previous research in this area [12,38], which has applied limited tailoring of message content for SMS-based brief interventions. Participants in this trial have been screened multiple times for risky drinking behavior, and as such, are an ideal cohort to target with an intervention.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, looking ahead to the future, the smartphone can also be used as an intervention delivery platform. In previous work, we found that interactive text messages were successful in reducing heavy drinking episodes among young adults [58][59][60][61].…”
Section: Esm Serves As "Ground Truth" For Drinking Behaviormentioning
confidence: 89%
“…The University of Pittsburgh Institutional Review Board approved study procedures. The trial was registered at http://www.clinicaltrials.gov:NCT01688245 and the protocol is described in detail in a prior publication 16 .…”
Section: Methodsmentioning
confidence: 99%